Review of Leading Lesson Study: A Practical Guide for Teachers and Facilitators - Jay Allen Babcock (Networks: An Online Journal for Teacher Research, 2011)
Put very simply, “[l]esson study is a professional development practice in which teachers collaborate to develop a lesson plan, teach, and observe the lesson to collect data on student learning, and [in which they] use their observations to refine their lesson” (p. 2). The approach was first developed in Japan and this book is just what the title purports it to be―a guide for teachers and facilitators who would like to bring this style of continuous professional development to their own classrooms. This book is for current in-service teachers who want to be involved with Lesson Study. All teachers wishing to improve by reflecting upon their teaching and improving their professional practice will benefit from this book. This book is not a collection of lessons plans; but rather, it is a guide towards becoming more reflective in one's own practice.